THE INFLUENCE OF VIRAL MARKETING DIMENSIONS AND PERCEIVED PRODUCT VALUE ON CUSTOMER SATISFACTION IN BURGER KING MANADO - Jifi Liow; Willem J. A. Tumbuan; Emilia M. Gunawan (Universitas Sam Ratulangi, 2023)
This study aims to identify if information spreading, economic incentives and perceived product value influence the customer satisfaction simultaneously. Identify if information spreading influence the customer satisfaction, if economic incentives influence the customer satisfaction, if perceived product value influence the customer satisfaction. to determine the effect of Viral Marketing Dimensions and Goods Value Assessment on Customer Satisfaction at Burger King Manado This study uses quantitative methods. To achieve this goal, the researchers distributed questionnaires and the sample used was 100 respondents. The data or results from this study were obtained directly from a questionnaire distributed to 100 respondents, in this case the customers of Burger King. The Influence of variable Information Spreading (X1) on variable Customer Satisfaction (Y).The results showed that information spreading as part of viral marketing dimension has positive impact toward purchase intention.Information Spreading as part of Viral Marketing Dimensions partially, brand Association as part of Viral Marketing Dimensions partially, Perceived Product Value partially, also Viral Marketing Dimensions (Information Spreading and Brand Association) and Peceived Product Value simultaneously have effect on customer satisfaction on Burger King Manado. Keywords: viral marketing, perceived product value, customer satisfaction